Implementation in Generic Environments - James Bergin; Arunava Sen (Queen's University, Department of Economics, 1992)
In this paper, we study implementation in "economic environments". It is shown that there is a dense subset of the set of preference profiles such that given an arbitrary social choice function, f and e > 0, there exits another social choice function g, g within e of f uniformly, and g implementable in Nash equilibrium on the dense subset.
Keywords: 330